Restitution of infectivity to spikeless vesicular stomatitis virus by solubilized viral components. - Bishop, D H (1975)
Noninfectious spikeless particles have been obtained from vesicular stomatitis virus (VSV, Indiana serotype) by bromelain or Pronase treatment. They lack the viral glycoprotein (G) but contain all the other viral components (RNA, lipid, and other structural proteins). Triton-solubilized VSV-Indiana glycoprotein preparations, containing the viral G protein as well as lipids (including phospholipids), have been extracted from whole virus preparations, freed from the majority of the detergent, and used to restore infectivity to spikeless VSV. The infectivity of such particles has been found to be enhanced by poly-L-ornithine but inhibited by Trition or homologous antiserum pretreatment. Heat-denatured glycoprotein preparations were not effective in restoring the infectivity to spikeless VSV. Heterologous glycoprotein preparations from the serologically distinct VSV-New Jersey serotype were equally capable of making infectious entities with VSV-Indiana spikeless particles, and the infectivity of these structures was inhibited by VSV-New Jersey antiserum but not by VSV-Indiana antiserum. Purified, detergent-free glycoprotein selectively solubilized from VSV-Indiana by the dialyzable detergent, octylglucoside, also restored infectivity of spikeless virions of VSV-Indiana and VSV-New Jersey.